Past, present, and future geo-biosphere interactions on the Tibetan Plateau and implications for permafrost - Ehlers, T.A.; Chen, D.; Appel, E.; Bolch, T.; Chen, F.; Diekmann, B.; Dippold, M.A.; Giese, M.; Guggenberger, G.; Lai, H.-W.; Li, X.; Liu, J.; et al. (Earth-Science Reviews, 2022)
Funding: This manuscript resulted from a Workshop in 2019 at the Senckenberg Research Institute and Natural History Museum Frankfurt, Germany, supported by the Strategic Priority Research Program of the Chinese Academy of Sciences (Grant No. XDA20100300). J. Liu also thanks the support of the Henan Provincial Key Laboratory of Hydrosphere and Watershed Water Security. T. Ehlers thanks the California Institute of Technology Moore Distinguished Scholar Program for support in completing this manuscript during a sabbatical. J. Liu and T. Bolch thank the support from the Strategic Priority Research Program of the Chinese Academy of Sciences (grants no. XDA20060402, XDA20100300). We thank the German Science Foundation (DFG) for support of the TiP (Tibetan Plateau: Formation-Climate-Ecoystems) priority research program (SPP-1372) for initiating the collaborations that led to this manuscript. Interactions between the atmosphere, biosphere, cryosphere, hydrosphere, and geosphere are most active in the critical zone, a region extending from the tops of trees to the top of unweathered bedrock. Changes in one or more of these spheres can result in a cascade of changes throughout the system in ways that are often poorly understood. Here we investigate how past and present climate change have impacted permafrost, hydrology, and ecosystems on the Tibetan Plateau. We do this by compiling existing climate, hydrologic, cryosphere, biosphere, and geologic studies documenting change over decadal to glacial-interglacial timescales and longer. Our emphasis is on showing present-day trends in environmental change and how plateau ecosystems have largely flourished under warmer and wetter periods in the geologic past. We identify two future pathways that could lead to either a favorable greening or unfavorable degradation and desiccation of plateau ecosystems. Both paths are plausible given the available evidence. We contend that the key to which pathway future generations experience lies in what, if any, human intervention measures ...